Perceptual Learning in Detoxified Alcoholic Men: Contributions From Explicit Memory, Executive Function, and Age. - Rosemary Fama (Alcoholism: Clinical & Experimental Research, 2004)
BACKGROUND:: Visuospatial and visuoperceptual deficits have consistently been observed in detoxified alcoholics; however, the severity of impairment varies with test and task type. Identifying the component processes and factors that underlie a particular deficit may reveal why some visuospatial and visuoperceptual tasks are more compromised than others and may lead to the specification of neural systems that are particularly vulnerable in alcoholism.METHODS:: We examined visuoperception and perceptual learning with a picture fragment identification task in 51 recently detoxified nonamnesic alcoholic men (aged 29–66 years) compared with 63 normal control men (aged 21–70 years). Executive function and explicit declarative memory were also assessed.RESULTS:: Despite deficits in the primary components of visuoperception and explicit memory for visuospatial stimuli, the alcoholics showed normal perceptual learning. Although the alcoholics and controls performed at comparable levels on the perceptual learning task, multiple regression analyses indicated that the factors accounting for perceptual learning variance differed between and within groups. Visuoperceptual abilities consistently predicted perceptual learning in the control subjects but not the alcoholic subjects. Explicit memory contributed to perceptual learning performance in both the alcoholic and control groups. Frontal executive ability consistently predicted perceptual learning in the alcoholic subjects, but it had predictive ability only in the control subjects as time elapsed. Age was significantly correlated with perceptual learning performance in both groups. Lifetime alcohol consumption, but not alcoholism duration, was an independent predictor of 1-hr perceptual learning.CONCLUSIONS:: These correlational analyses suggest that controls invoke basic visuospatial processes to perform a perceptual learning task, whereas alcoholics invoke higher-order cognitive processes (i.e., frontal executive systems) to perform the same task at normal levels. Use of more demanding cognitive systems by the alcoholics may be less efficient and more costly to processing capacity than those invoked by controls.